2015
DOI: 10.1016/j.cell.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability as a Function of Purifying Selection in TEM-1 β-Lactamase

Abstract: Evolvability—the capacity to generate beneficial heritable variation—is a central property of biological systems. However, its origins and modulation by environmental factors have not been examined systematically. Here, we analyze the fitness effects of all single mutations in TEM-1 β-lactamase (4,997 variants) under selection for the wild-type function (ampicillin resistance) and for a new function (cefotaxime resistance). Tolerance to mutation in this enzyme is bimodal and dependent on the strength of purify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
382
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(408 citation statements)
references
References 63 publications
24
382
1
1
Order By: Relevance
“…However, the findings here are consistent with data in at least one other protein system-TEM-1 b-lactamase, an enzyme that confers resistance to specific antibiotics in bacteria (Salverda et al, 2010). Deep mutational scanning reveals a class of mutations underlying adaptation that shows conditional neutrality; that is, neutral with regard to the existing substrate but gain of function toward a new substrate (Stiffler et al, 2015). As in PSD95 pdz3 , these mutations occur at sites that are distant from the active site, connecting through physically contiguous networks within the protein structure.…”
Section: A Structural Model For Protein Adaptationsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the findings here are consistent with data in at least one other protein system-TEM-1 b-lactamase, an enzyme that confers resistance to specific antibiotics in bacteria (Salverda et al, 2010). Deep mutational scanning reveals a class of mutations underlying adaptation that shows conditional neutrality; that is, neutral with regard to the existing substrate but gain of function toward a new substrate (Stiffler et al, 2015). As in PSD95 pdz3 , these mutations occur at sites that are distant from the active site, connecting through physically contiguous networks within the protein structure.…”
Section: A Structural Model For Protein Adaptationsupporting
confidence: 89%
“…Recent high-throughput methods for mutagenesis (Fowler and Fields, 2014;McLaughlin et al, 2012;Stiffler et al, 2015) will facilitate testing of the generality of this conclusion. However, the findings here are consistent with data in at least one other protein system-TEM-1 b-lactamase, an enzyme that confers resistance to specific antibiotics in bacteria (Salverda et al, 2010).…”
Section: A Structural Model For Protein Adaptationmentioning
confidence: 91%
“…However, how the constraining effects of such genetic interactions are affected by environmental variability remains poorly understood. It has been shown that mutational effects (30)(31)(32)(33) and epistasis itself (34,35) can depend on the environment, that bacterial resistance evolution can be contingent on the rate of antibiotic increase (36), and that adaptation in silico can be accelerated by environmental change (37)(38)(39)(40). These observations suggest that the effects of environmental variability may go beyond merely producing variable selective pressures that favor certain phenotypes but also, could be involved in controlling phenotype accessibility and stasis.…”
mentioning
confidence: 87%
“…We obtained site-specific fitness parameters for the second simulation data set using Mutation-Selection Model Performance . doi:10.1093/molbev/msw171 MBE amino-acid propensities measured experimentally using deep-mutational scanning (DMS) (Bloom 2014a;Firnberg et al 2014;Stiffler et al 2014;Thyagarajan and Bloom 2014;Doud et al 2015;Kitzman et al 2015). Derivation of simulation parameters is described in depth in Materials and Methods.…”
Section: Simulation and Inference Approachmentioning
confidence: 99%
“…The genes used were influenza H1N1 hemagglutinin (Thyagarajan and Bloom 2014), influenza nucleoprotein (Bloom 2014a;Doud et al 2015), TEM-1 b-lactamase (Firnberg et al 2014;Stiffler et al 2014), and yeast Gal4 (Kitzman et al 2015). We specifically used scaled experimental amino-acid propensities, as given by and described in Bloom (2016).…”
Section: Generation Of Simulated Datamentioning
confidence: 99%